2020
DOI: 10.1213/ane.0000000000005162
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Anesthesia Severe Adverse Events Leading to Anesthetic Morbidity and Mortality in a Tertiary Care Center in a Low- and Middle-Income Country: A 25-Year Audit

Abstract: Background: The analysis of adverse events, including morbidity and mortality (M&M), helps to identify subgroups of children at risk and to modify clinical practice. There are scant data available from low- and middle-income countries. Our aim was to estimate the proportion of pediatric patients with various severe adverse events in the perioperative period extending to 48 hours and to describe the clinical situations and causes of those events. METHODS: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…The finding that the overall incidence of SARCIs in our study was 3 times higher than in HICs and that respiratory events predominate was not unexpected. 1–5,9,11,15–17,25,26 Similar to other studies, we identified 4 independent risks associated with RCIs, those being younger age group, increasing ASA physical status, preoperative respiratory infection, and airway management with an ETT. 5,27 Despite high use of inhalational inductions in our study compared to von Ungern-Sternberg et al 27 (76% vs 39%), we did not identify inhalational induction, or otorhinolaryngology surgery (ENT) as independent risks associated with RCI.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The finding that the overall incidence of SARCIs in our study was 3 times higher than in HICs and that respiratory events predominate was not unexpected. 1–5,9,11,15–17,25,26 Similar to other studies, we identified 4 independent risks associated with RCIs, those being younger age group, increasing ASA physical status, preoperative respiratory infection, and airway management with an ETT. 5,27 Despite high use of inhalational inductions in our study compared to von Ungern-Sternberg et al 27 (76% vs 39%), we did not identify inhalational induction, or otorhinolaryngology surgery (ENT) as independent risks associated with RCI.…”
Section: Discussionsupporting
confidence: 83%
“…Despite the differences in reported rates across country income categories, common themes emerge regarding types and risks for SARCIs. Perioperative respi-ratory critical incidents (RCIs) predominate, 1–5,9,11,15–17 while younger age, preexisting medical history (especially respiratory comorbidities), higher American Society of Anesthesiologists (ASA) physical status, 5 and emergency surgery are commonly identified risks for SARCIs. 3,5,16…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The authors concluded that increased access to anesthetic drugs and practice improvements resulted in a decline in perioperative cardiac arrests. 15 Pediatric Anesthesia Training Infrastructure Assessment in any medical disciplines requires an infrastructure in terms of list numbers and available equipment and supervision, as well as elements of how the training is delivered, such as quality, content and frequency of lectures, workshops, case-based discussion, simulation training, clinical skills training, etc. Our survey focused only on the provision of infrastructure and not the quality.…”
Section: Pediatric Anesthesia Servicesmentioning
confidence: 99%
“…1,11,15,16 The time-based definition of PPOCA differs among studies, ranging from cardiac arrests occurring in the postanaesthesia care unit (PACU) 3,5,10,12,16 -19 or 60 min after anesthesia 2,6 until 24 1,7,8,15 to 48 h after completion of anaesthesia. 13 However, settings for patient care and monitoring during anaesthesia and in the postoperative period such as the PACU, intensive care unit (ICU), and ward, are different in different locations. For example, in the operating room, continuous monitoring and the presence of anaesthesia providers at all times are considered the standard of care.…”
Section: Introductionmentioning
confidence: 99%